Volume 7: Fluids and Heat Transfer, Parts A, B, C, and D 2012
DOI: 10.1115/imece2012-88817
|View full text |Cite
|
Sign up to set email alerts
|

Data Center Cooling Efficiency Improvement Through Localized and Optimized Cooling Resources Delivery

Abstract: Data centers are large computing facilities that can house tens of thousands of computer servers, storage and networking devices. They can consume megawatts of power and, as a result, reject megawatts of heat. For more than a decade, researchers have been investigating methods to improve the efficiency by which these facilities are cooled. One of the key challenges to maintain highly efficient cooling is to provide on demand cooling resources to each server rack, which may vary with time and rack location with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The airflow of the inlet air is a mix of recirculated hot air exhausted from other servers and supplied cool air from CRACs. The time-discrete form of rack inlet temperature is as follows [9], [28]:…”
Section: Cooling Modelsmentioning
confidence: 99%
“…The airflow of the inlet air is a mix of recirculated hot air exhausted from other servers and supplied cool air from CRACs. The time-discrete form of rack inlet temperature is as follows [9], [28]:…”
Section: Cooling Modelsmentioning
confidence: 99%
“…However, the approach failed to minimize the overall energy consumption of the systems and fans. Zhou et al studied the improvement of cooling efficiency through localized and optimized cooling resources [26]. Zhou et al suggested to use adaptive vent tiles mounted on floor and control cooling provisions to reduce costs [26].…”
Section: Optimization Approaches For System Efficiency In Sustainablementioning
confidence: 99%
“…Zhou et al studied the improvement of cooling efficiency through localized and optimized cooling resources [26]. Zhou et al suggested to use adaptive vent tiles mounted on floor and control cooling provisions to reduce costs [26]. However, the suggestion did not consider the power consumption of cooling fans.…”
Section: Optimization Approaches For System Efficiency In Sustainablementioning
confidence: 99%
See 2 more Smart Citations